Implementation of Tax Practices on Zakat as a Solution to Increase Zakat Effectiveness in Indonesia - Pujiati Pujiati; Chandra Warsito (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Taxes and zakat are two sources of receipt of very significant sources of state income in Indonesia, both of which have the same element of coercion and management elements, while the difference is in the name, object, nature of obligations, legal basis, magnitude and utilization. This research aims to provide an overview of the similarities and differences between the concept of taxes and zakat, the arguments of scholars about taxes and zakat and also provide an overview of the effectiveness of effective management and zakat based on the implementation of the management of tax practices that have been running in the country of Indonesia. The findings in this paper show several different management between the concept of tax and zakat. The effectiveness of existing tax management has increased while zakat is the opposite. Implementation of tax management practices that can be applied as a solution to increase the effectiveness of zakat is the application of sanctions on negligent managers and muzakki, the management of HR management, the implementation of effective and efficient zakat administration (in terms of function, the existence of good systems, programs and institutions), the existence of good information systems and the existence of independent institutions as special auditors